Endometriosis as a Chronic Disease - Impact on Patients Quality of Life - Hobot, Maciej; Strzałkowska, Paulina; Grabski, Wojciech; Kosiński, Maciej; Szaj, Dominika; Raczkowska, Michalina; Szymajda, Wiktor; Trojańska, Aleksandra; Kaźmierczak, Monika (Quality in Sport, 2025)
Endometriosis is a chronic gynecological condition marked by the presence of endometrial-like cells outside the uterine cavity, most commonly affecting the ovaries, fallopian tubes, and peritoneum. Despite an estimated prevalence of 10% among women of reproductive age, the condition is often underdiagnosed and underrecognized. Many women endure years of symptoms before receiving an accurate diagnosis, resulting in prolonged physical suffering and significant disruption to daily life. Common symptoms include severe menstrual pain, dyspareunia, chronic pelvic pain, fatigue, and infertility. Due to their cyclical and persistent nature, these symptoms negatively affect women’s physical and mental health, social functioning, relationships, and professional life. As there is no definitive cure and symptoms often recur, endometriosis is classified as a chronic illness requiring a comprehensive care approach. This paper explores the multifaceted impact of endometriosis on quality of life and examines key assessment tools such as SF-36, WHOQOL-BREF, and EHP-30. It also includes an overview of current treatment strategies - both pharmacological and surgical - as well as supportive and non-pharmacological approaches. The need for an individualized and multidisciplinary model of care is emphasized to improve outcomes and support the overall well-being of affected women.